Students’ Perspectives on Learning Vocabulary Using Board Race - Nanda Listiyawati; Dodi Mulyadi; Muhimatul Ifadah (Proceedings Series on Social Sciences & Humanities, 2024)
This study explores the unique lens of students' perspectives on vocabulary acquisition within the context of a board game race. Utilizing a qualitative research design, data were collected through survey and interview to gain comprehensive insights into students' experiences. Results indicate a high level of enthusiasm and engagement among students participating in the board game race, highlighting the motivational impact of gamification on vocabulary acquisition. The interactive and competitive nature of the game not only fostered a positive learning environment but also encouraged collaboration and camaraderie among students. The study delves into the perpective students of the board game race in enhancing vocabulary comprehension, retention, and application. Students appreciate the contextualization of words within the game scenarios, emphasizing the practicality of acquired vocabulary in real-life situations. In conclusion, this research sheds light on the positive of board game races on students' perspectives toward vocabulary learning, offering educators a foundation for leveraging gamification as a dynamic and effective tool in language acquisition.